2022
DOI: 10.1007/s10389-022-01743-x
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for attributes of long-term care in dementia: a scoping review of multi-criteria decision analyses

Abstract: Aim Long-term care considerations for persons with dementia are complex. Multi-criteria decision analysis (MCDA) methods are increasingly used to support healthcare decisions. The objective of this scoping review was to identify and analyze published MCDAs in which preferences for living and care concepts for persons with dementia are determined. Subject and methods A literature search was conducted in PubMed, EMBASE, Web of Science, and Google Scholar in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Attributes and levels were developed following the recommendations by Helter and Boehler [ 40 ], namely raw data collection, data reduction, removing inappropriate attributes, and wording. A scoping review was conducted to collate published studies in which preferences for living and care concepts for persons with dementia are determined [ 14 ], and a systematic review identified studies assessing innovative forms of housing for persons with dementia [ 41 ]. Based on the results of these reviews, focus groups with participants from the general public aged 50 years and older aimed to identify important aspects of care arrangements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attributes and levels were developed following the recommendations by Helter and Boehler [ 40 ], namely raw data collection, data reduction, removing inappropriate attributes, and wording. A scoping review was conducted to collate published studies in which preferences for living and care concepts for persons with dementia are determined [ 14 ], and a systematic review identified studies assessing innovative forms of housing for persons with dementia [ 41 ]. Based on the results of these reviews, focus groups with participants from the general public aged 50 years and older aimed to identify important aspects of care arrangements.…”
Section: Methodsmentioning
confidence: 99%
“…Small-scale homelike living units usually offer group living for 5–15 residents with dementia and put an emphasis on residents’ choices, autonomy and independence [ 10 , 13 ]. A number of studies have shown that compared with more traditional settings, small-scale homelike living units may encourage social behaviour, preserve activity performance and positively influence emotional status, while other studies have failed to show these effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation